A Stability Indicating Reverse Phase High Performance Liquid Chromatography Method for Related Substances of Sofosbuvir in Tablet Dosage Form (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Sofosbuvir is an antiviral drug that is used to treat hepatitis C. A present investigation deals with simple, sensitive, rapid, precise and accurate reverse phase high-performance chromatography (RP-HPLC) method developed and validated for related substances of sofosbuvir in tablet dosage form. The chromatographic separation was achieved on a Kromasil 100 C18 (250 × 4.6 mm, 5 μ) column. A sofosbuvir and its impurities were extracted by composed mixture of Mobile Phase A: buffer solution: acetonitrile (97.5:2.5% v/v) and Mobile Phase B: acetonitrile, isopropyl alcohol, methanol and purified water (60:20:10:10 % v/v/v/v) using with flow rate was 1-mL/min, column temperature was 25°C, injection volume was 10 μL, Vial thermostat temperature was 10°C. The UV detection was carried out at 263 nm. The retention time of sofosbuvir, methyl ester and ethyl ester were 54.28, 36.31 and 43.77, respectively. The method shows linearity with correlation coefficient of sofosbuvir and its impurity was 0.999 over the 0.5–7.5 ppm range. The average recovery was found to be 90.2–113.9%. The LoD and LoQ for sofosbuvir and its impurities were found to be 0.1 and 0.5 μg/mL, respectively. The method was validated as per ICH guidelines. The developed method was precise, accurate, novel and detectable towards sofosbuvir and its impurity. This method is efficient in separating the sofosbuvir and its impurity. Hence, the proposed method can be utilized for the determination of related substances in routine analysis in quality control department of pharmaceutical Industry.